New Value: Keeping It Real - Peter Chamberlain (Journal of Visual Art and Design, 2013)
Many parts of the world now swim in a sea of complex products that do not necessarily improve the overall quality of our lives. From cell phones to baby strollers, we have overloaded our designed environment with hyper-functional products that often leave us searching for simpler, straighter forward product offerings. In a product landscape that more often than not equates complexity with sophistication; our ever-increasingly complex modern society has allowed faux conveniences to outweigh the tangible realness of our experiences. The look and feel of products has often become complex and complicated "“ and this is often highlighted as a positive thing. We are less likely to encounter simple, intuitive, and usable products geared toward the individual. To avoid this trap, one would need to apply a filter that would govern the intake of certain products to only those that are seen as adding true value to our lives. It is necessary to appeal to people's emotions, and carry cultural richness and authenticity back to the forefront while embracing the power of cur-rent and future technologies. Design has tremendous power and the versatility necessary to bring about this positive change.